2019
DOI: 10.1101/576942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sodium nitroprusside prevents the detrimental effects of glucose on the neurovascular unit and behaviour in zebrafish

Abstract: Diabetes is associated with dysfunction of the neurovascular unit, although the mechanisms of this are incompletely understood, and currently no treatment exists to prevent these negative effects. We previously found that the NO donor sodium nitroprusside (SNP) prevents the detrimental effect of glucose on neurovascular coupling in zebrafish. We therefore sought to establish the wider effects of glucose exposure on both the neurovascular unit and on behaviour in zebrafish and the ability of SNP to prevent thes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…However, transgenic zebrafish reporters for visualizing all types of mural cells have not been available to investigators, hampering our understanding of the complex processes underlying mural cell development and subsequent vascular maturation steps. It is noteworthy, however, that several mural cell reporter lines have been developed in the last decade in our and other labs ( Table 1 ), allowing us to achieve a better understanding of mural cell development and functions [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, transgenic zebrafish reporters for visualizing all types of mural cells have not been available to investigators, hampering our understanding of the complex processes underlying mural cell development and subsequent vascular maturation steps. It is noteworthy, however, that several mural cell reporter lines have been developed in the last decade in our and other labs ( Table 1 ), allowing us to achieve a better understanding of mural cell development and functions [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rats showed absent or negative blood-oxygen-level-dependent (BOLD) signals in functional magnetic resonance imaging (fMRI) with increased BOLD signals 2–3 weeks postnatally [ 348 , 349 ]. In zebrafish NVC develops between 6-to-8dpf and high glucose exposure impairs NVC, mirroring human diabetes [ 350 , 351 ].…”
Section: Non-endothelial Cells Required For Cerebrovascular Developmentmentioning
confidence: 99%